Cross-resistance of the diamondback moth indicates altered interactions with domain II of Bacillus thuringiensis toxins. - Tabashnik, B E (1996)
We compared responses to six insecticidal crystal proteins from Bacillus thuringiensis by a Cry1A-resistant strain (NO-QA) and a susceptible strain (LAB-P) of the diamondback moth, Plutella xylostella. The resistant strain showed > 100-fold cross-resistance to Cry1J and to H04, a hybrid with domains I and II of Cry1Ab and domain III or Cry1C. Cross-resistance was sixfold to Cry1Bb and threefold to Cry1D. The potency of Cry1I did not differ significantly between the resistant and susceptible strains. Cry2B did not kill resistant or susceptible larvae. By combining these new data with previously published results, we classified responses to 14 insecticidal crystal proteins by strains NO-QA and LAB-P. NO-QA showed high levels of resistance to Cry1Aa, Cry1Ab, and Cry1Ac and high levels of cross-resistance to Cry1F, Cry1J, and H04. Cross-resistance was low or nil to Cry1Ba, Cry1Bb, Cry1C, Cry1D, Cry1I, and Cry2A. Cry1E and Cry2B showed little or no toxicity to susceptible or resistant larvae. In dendrograms based on levels of amino acid sequence similarity among proteins, Cry1F and Cry1J clustered together with Cry1A proteins for domain II, but not for domain I or III. High levels of cross-resistance to Cry1Ab-Cry1C hybrid H04 show that although Cry1C is toxic to NO-QA, domain III or Cry1C is not sufficient to restore toxicity when it is combined with domains I and II of Cry1Ab. Thus, diamondback moth strain NO-QA cross-resistance extends beyond the Cry1A family of proteins to at least two other families that exhibit high levels of amino sequence similarity with Cry1A in domain II (Cry1F and Cry1J) and to a protein that is identical to Cry1Ab in domain II (H04). The results of this study imply that resistance to Cry1A alters interactions between the insect and domain II.